The Referee of Charity on Different Religions: A Comparative and Jurisprudence Study - Ahmad aljaburi, Jaefar Muhammad (Journal of Tikrit University for Humanities, 2022)
Charity to the people of religions is one of the important topics that we need to study and spread among the nations so that the far and near can see the tolerance of our true religion and its valuable principles. among the nations; Among this comprehensive view of the tolerance of Islam is giving charity to the people of religions; Because of the importance of this topic, I wanted to write about it. Let me explain the ruling on this issue in a comparative manner among the jurists, as well as what prompted me to write on this subject that the world is experiencing a kind of conflict at various levels and in all fields, the most dangerous of which is the religious conflict, and there is a strong attack against Islam and Muslims and many attempts; In order to distort the image of Islam among non-Muslims, and describe Islam as a religion of extremism and terrorism, and the assimilation of the rights of others, I wanted to clarify the ruling on this issue through which the tolerance of Islam and its view of coexistence with people of other religions appears through a jurisprudential study of this issue.